Evaluation of spin in the abstracts of systematic reviews and meta-analyses covering surgical management, or quality of life after surgical management, of osteoarthritis of the knee. Issue 4 (December 2020) - Siex, Parker; Nowlin, William; Ottwell, Ryan; Arthur, Wade; Checketts, Jake; Thompson, Jay; Small, Travis; Reddick, Brad; Wright, Drew N.; Hartwell, Micah; Chen, Suhao; Miao, Zhuqi; et al.
Abstract: Objective: Our primary objective was to identify the prevalence of spin — misleading reporting practices that overemphasize benefit or underemphasize harm — within the abstracts of systematic reviews and meta-analyses focused on surgical management of osteoarthritis of the knee. Methods: A search string was developed to search Ovid MEDLINE and Ovid Embase for articles pertaining to surgical management, or quality of life after surgical management, of osteoarthritis of the knee. Titles and abstracts were screened according to our protocol, developed a priori, followed by full-text evaluation for spin in included articles. Study characteristics were simultaneously extracted with spin data and each included study received an AMSTAR-2 quality appraisal. All procedures were performed by two examiners in a masked, duplicate fashion. Results: Of the 1419 articles returned, 96 systematic reviews qualified for inclusion. 35.4% of the included abstracts (34/96) contained at least one type of spin with a total of 36 occurrences (two abstracts contained two types of spin). Selective reporting favoring benefit (type 3; 15/36, 41.7%) was the most prevalent followed by selective reporting of harms (type 6; 7/36, 19.4%). None of the abstracts contained spin types 2, 4, or 8. We found no significant association between spin and either AMSTAR-2 rating or extracted study characteristics. Conclusion: Of the included systematic reviews and meta-analyses, 35.4% contained spin in their abstract. To improve the reliability of systematic reviews and meta-analyses, researchers should act to minimize spin in future abstracts.